Pengaruh Fear of Missing Out (FoMO) dan Halal awareness Terhadap Keputusan Pembelian Skincare Korea pada Generasi Z di Surabaya - Haryono, Aufa Aviska (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Fear of missing out (FoMO) and Halal awareness on the purchasing decisions of Korean skincare products among Generation Z in Surabaya. This research uses a quantitative method with an associative approach. Data were collected through the distribution of questionnaires to 100 respondents aged 17–27 years who reside in Surabaya and have experience using Korean skincare products. The data analysis technique employed is multiple linear regression with the assistance of SPSS. The results of the study show that both FoMO and Halal awareness have a significant influence on purchasing decisions. Furthermore, FoMO and Halal awareness simultaneously have a significant effect on purchasing decisions. This study contributes to the understanding of Generation Z consumer behavior, particularly in the context of halal product marketing and global trends.